Comparative feeding strategies of yellowfin tuna around St Helena and adjacent seamounts of the South Atlantic Ocean. (18th October 2020) - Laptikhovsky, Vladimir; Naulaerts, Joachim; Clingham, Elizabeth; Collins, Martin A.; Cranfield, Martin; Henry, Leeann; Small, Alison; Stamford, Tammy; Xavier, Jose; Wright, Serena
Abstract: Yellowfin tuna are the mainstay of the traditional tuna fisheries in St Helena waters, but there is limited knowledge of their ecology and feeding behaviour in the area. In this study yellowfin tuna stomach contents were used to assess spatio‐temporal changes in feeding strategy and consider the role of tuna in the local ecosystem. Comparisons of the feeding spectra of yellowfin tuna between inshore regions of St Helena and oceanic seamounts demonstrated that in both areas the species was largely piscivorous. In inshore waters yellowfin consumed more neritic fauna, including significant numbers of crab megalopa, whereas around seamounts the diet included a greater diversity of epi‐ and mesopelagic fish and squids. The most important fish prey species in inshore waters was the St Helena butterflyfish Chaetodon sanctahelenae, and around seamounts was the pufferfish Lagocephalus lagocephalus . Results indicate that the diet spectrum of yellowfin tuna in St Helena waters is relatively similar to those of conspecifics living in waters with relatively low productivity, with strategies indicative of food‐poor ecosystems. The availability of coastal fauna may make areas around islands and seamounts more attractive for feeding aggregations of yellowfin tuna, compared to the open ocean. The relatively unselective feeding of yellowfin tuna means that stomachs can provide valuable data on the species diversity, particularly in remote areas with limited opportunities for dedicated research expeditions.